The Effect of Gross Regional Domestic Product and Human Development Index on Economic Growth - Arrafiqi, Laksamana Aulia Fahmi; Arifin, Atwal (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study analyzes the effect of Gross Regional Domestic Product, Human Development Index, and Open Unemployment Rate on economic growth in Central Java Province during the period 2020-2022. Using panel data from 35 districts/cities, the purposive sampling method is applied to capture regional economic disparities. The analysis was carried out using a panel data regression model, using the Random Effect Model, Fixed Effect Model, and Common Effect Model which were validated through the Chow and Hausman tests. The results showed that Gross Regional Domestic Product had a significant effect on economic growth (p <0.05), while Human Development Index had a significant but negative effect on economic growth. Conversely, did not have a significant effect on these variables (p>0.05). These findings underline the importance of improving the quality of human resources and managing GRDP to support economic growth, although unemployment is not always a direct determinant. The practical implication of this study is the need for policies focused on increasing productivity and resource management to support sustainable growth in Central Java.